2021
DOI: 10.3390/ijms222011062
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation and Post-Translational Modifications of SNAI1 in Cancer Metastasis

Abstract: SNAI1, a zinc finger transcription factor, not only acts as the master regulator of epithelial-mesenchymal transition (EMT) but also functions as a driver of cancer progression, including cell invasion, survival, immune regulation, stem cell properties, and metabolic regulation. The regulation of SNAI1 occurs at the transcriptional, translational, and predominant post-translational levels including phosphorylation, acetylation, and ubiquitination. Here, we discuss the regulation and role of SNAI1 in cancer met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 104 publications
2
14
0
Order By: Relevance
“…Through EMT induction, epithelial cells undergo cytoskeletal reorganization, engage in extracellular matrix (ECM) remodeling, and become more mobile and invasive, detaching from surrounding cells and the ECM ( 20 ). These changes coincide with a reduction in the expression of epithelial marker proteins and the upregulation of mesenchymal marker proteins including Vimentin and N-cadherin, with this process being regulated by key transcription factors including members of the TWIST, SNAIL, and ZEB families ( 21 , 22 ). Prior studies have shown ECM1 to play a role in this EMT process in several epithelial malignancies, thereby promoting metastatic progression.…”
Section: Discusionmentioning
confidence: 97%
“…Through EMT induction, epithelial cells undergo cytoskeletal reorganization, engage in extracellular matrix (ECM) remodeling, and become more mobile and invasive, detaching from surrounding cells and the ECM ( 20 ). These changes coincide with a reduction in the expression of epithelial marker proteins and the upregulation of mesenchymal marker proteins including Vimentin and N-cadherin, with this process being regulated by key transcription factors including members of the TWIST, SNAIL, and ZEB families ( 21 , 22 ). Prior studies have shown ECM1 to play a role in this EMT process in several epithelial malignancies, thereby promoting metastatic progression.…”
Section: Discusionmentioning
confidence: 97%
“…Similarly, in the current investigation, gene expression of SMAD3 and SMAD4 was significantly reduced in the tumours of the patients with underlying COPD. This signalling pathway may play an important role in the initiation of a profibrogenic effect through TGF-β signalling in patients with COPD, thus favouring lung carcinogenesis [ 12 , 27 ]. As such the downregulation of the EMT repressor SMAD pathway may favour a pro-tumoural micro-environment in patients with chronic airways diseases, namely COPD, which could be targeted therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial–mesenchymal transition (EMT) is a biological process characterised by the loss of polarity and cell–cell adhesion of epithelial cells to gain invasive characteristics. The transformed epithelial cells become mesenchymal stem cells, which can differentiate into a great variety of cell types [ 11 , 12 ]. EMT is a physiological process involved in organ development in the embryo and in wounds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the list of TFs has been updated, and new findings in the complex regulatory network they form were recently summarized (Debnath et al, 2022). Regarding Snail-1, the involvement of the B-Raf proto-oncogene (BRAF) gene was highlighted, linked with chemoresistance in thyroid cancer (Wieczorek-Szukala and Lewinski, 2021), and the role of epigenetic regulation was emphasized (Dong and Wu, 2021). Even more important, Snail-1 was shown to be involved in tumor immunosuppression by inducing chemokines and immunosuppressive cells into the tumor microenvironment (Tang et al, 2021).…”
Section: Transcriptional and Translation Factorsmentioning
confidence: 99%